Keselarasan Antara Arah Bangunan dengan Arah Kiblat Masjid Bersejarah di Kabupaten Jember - Hakim, Alfian Nurul (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2025)
Several historic mosques, including one located in Jember Regency, exhibit qibla orientations that deviate from the ideal direction. This study aims to analyze the alignment between the architectural orientation and the qibla direction of historic mosques in Jember Regency. Data were obtained through field research methods, including direct observation, precise measurement, and systematic documentation. The architectural orientation and qibla direction of historic mosques in Jember Regency, based on data from the Ministry of Religious Affairs of the Republic of Indonesia’s SIMAS platform and measurements using Google Maps, show varying values in both orientation and deviation. Similar variations were also observed when using the Mizwala instrument. The alignment between the architectural orientation and the qibla direction of historic mosques in Jember Regency, as recorded in the SIMAS database of the Ministry of Religious Affairs of the Republic of Indonesia, indicates a consistent correspondence between the two. It is recommended that the Ministry of Religious Affairs or relevant institutions regularly update the data to ensure that the qibla direction information and related records in SIMAS accurately reflect current field conditions.